Pseudocetherinae (Hemiptera: Reduviidae) revisited: phylogeny and taxonomy of the lobe-headed bugs - Castillo, Stephanie; Rédei, Dávid; Weirauch, Christiane (European Journal of Taxonomy, 2022)
The concept of the previously monogeneric subfamily Pseudocetherinae (Hemiptera: Heteroptera: Reduviidae) is revised and expanded. We here transfer Gerbelius Distant, 1903, Kayanocoris Miller, 1954, Microvarus Jeannel, 1917, Paragerbelius Miller, 1958, and Voconia Stål, 1866 from Reduviinae to Pseudocetherinae and treat Kayanocoris, Microvarus, Paragerbelius, and Pseudocethera Villiers, 1963 as junior synonyms of Voconia, resulting in new combinations for Voconia conradti (Jeannel, 1917) comb. nov., V. ifana (Villiers, 1963) comb. nov., V. monodi (Villiers, 1963) comb. nov., V. motoensis (Schouteden, 1929) comb. nov., V. ornata (Distant, 1903) comb. nov., V. schoutedeni (Villiers, 1964) comb. nov., V. typica (Miller, 1958) comb. nov., and V. wegneri (Miller, 1954) comb. nov. We also describe 23 new species of Voconia: V. bakeri sp. nov., V. bracata sp. nov., V. brachycephala sp. nov., V. chrysoptera sp. nov., V. coronata sp. nov., V. decorata sp. nov., V. dolichocephala sp. nov., V. fasciata sp. nov., V. grandioculata sp. nov., V. hemera sp. nov., V. isosceles sp. nov., V. laosensis sp. nov., V. lasiosoma sp. nov., V. lirophleps sp. nov., V. loki sp. nov., V. mexicana sp. nov., V. minima sp. nov., V. nyx sp. nov., V. smithae sp. nov., V. tridens sp. nov., V. trinidadensis sp. nov., V. tuberculata sp. nov., and V. vittata sp. nov. Lectotypes are designated for Gerbelius confluens Distant, 1903, G. typicus Distant, 1903, V. conradti comb. nov., V. ornata comb. nov., and V. pallidipes Stål, 1866. A revised diagnosis and description of Pseudocetherinae are provided along with photographs of the species and of the male genitalia of 13 pseudocetherine and five closely related reduviine species. An identification key to the two genera of Pseudocetherinae as well as a key to species of Voconia are presented. A phylogenetic hypothesis is proposed for the relationships of Pseudocetherinae using parsimony analyses of 77 morphological characters.